2017
DOI: 10.1021/acs.nanolett.7b03332
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting Fano Resonances To Control Photonic–Plasmonic Hybridization

Abstract: Hybrid photonic-plasmonic systems have tremendous potential as versatile platforms for the study and control of nanoscale light-matter interactions since their respective components have either high-quality factors or low mode volumes. Individual metallic nanoparticles deposited on optical microresonators provide an excellent example where ultrahigh-quality optical whispering-gallery modes can be combined with nanoscopic plasmonic mode volumes to maximize the system's photonic performance. Such optimization, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 65 publications
1
59
0
Order By: Relevance
“…In excellent agreement with previous reports of several groups [27,28,30,34,35,40,41,129], hybrids can outperform the individual constituents in terms of Purcell factor, and can do so at any Q that bridges the gap between the antenna and high-Q cavity. Detuning allows one to choose Q while keeping F P almost constant.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In excellent agreement with previous reports of several groups [27,28,30,34,35,40,41,129], hybrids can outperform the individual constituents in terms of Purcell factor, and can do so at any Q that bridges the gap between the antenna and high-Q cavity. Detuning allows one to choose Q while keeping F P almost constant.…”
Section: Resultssupporting
confidence: 91%
“…Recently, several groups including our own suggested that hybrid plasmonic-dielectric resonators can be constructed [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], raising the idea that exactly this trade-off between confinement and Q can be reached. In this work we present a survey of the performance that should be available with hybrids if one assumes access to state-ofthe-art building block cavities and antennas.…”
Section: Introductionmentioning
confidence: 99%
“…The beating provides a rather complicated pattern that it is difficult to understand especially because it strongly depends on the near‐field position. Conversely, in the frequency domain, the spectrum exhibits a double dip often qualitatively interpreted as a Fano response resulting from the interference of out‐of‐phase modes that are difficult to identify especially when they overlap spectrally and spatially . The main strength of the QNM expansion is to provide a quantitative interpretation that unambiguously reveals the role and impact of each QNM by providing a direct access to the few control knobs, the QNM excitation coefficients that are driving the temporal response.…”
Section: Light Scattering By Resonant Systemsmentioning
confidence: 99%
“…This is a direct indication that collective effects put a limit on the achievable polarization in a sheet on basis of flux arguments: the total flux that the polarized sheet radiates and/or absorbs can never exceed the flux of the input field. This should be contrasted to reports for cavityantenna hybrids with single antennas [66][67][68], and to the notion of Ameling et al that plasmon array etalons allow to boost the sensitivity of, e.g., refractive index sensors, by combining high Q with enhanced fields [34][35][36][37]. It is only true for weakly scattering antennas that plasmon antenna enhancement and microcavity field enhancement effects add.…”
Section: Birefringent Salisbury Screensmentioning
confidence: 78%